Comparison of the Efficacy of Brolucizumab with Natural Disease Progression in Wet AMD Using Clinical Data from the Phase III HAWK and HARRIER Trials and Modelled Placebo Data. (2nd October 2020) - Agostini, Hansjürgen; Mulyukov, Zufar; Tsilimbaris, Miltiadis; Calvo, Pilar; Bucher, Felicitas; Gaucher, David; Pigeolet, Etienne; Colafrancesco, Valeria; Clemens, Andreas
ABSTRACT: Aim : To compare the treatment effect of brolucizumab, a novel anti–vascular endothelial growth factor therapeutic, with a putative placebo in patients with wet age-related macular degeneration. Materials and Methods : Clinical treatment-effect data from patients receiving brolucizumab 6 mg in the HAWK and HARRIER studies were compared with modelled placebo data using a previously developed and validated indirect response, non-linear, mixed effects model describing the natural visual acuity decline in wet age-related macular degeneration. The placebo model incorporated patient-level data from the sham injection arms of the MARINA and PIER studies, corrected for baseline best corrected visual acuity and age difference between these studies and the HAWK and HARRIER studies. Results : Compared with a modelled placebo, brolucizumab treatment was associated with an overall best corrected visual acuity gain of approximately 22 Early Treatment Diabetic Retinopathy Study letters at Week 48 and 28 letters at Week 96. Conclusions : As anti–vascular endothelial growth factor therapy is now a standard of care for wet age-related macular degeneration, it is not feasible to conduct placebo-controlled trials for new wet age-related macular degeneration treatments. By allowing comparison with the natural decline in visual acuity without treatment, this analysis conveys the clinical importance of brolucizumab for the treatment of wet age-related macular degeneration.